Resident memory CD8(+) T cells dominate lymphoid immune cell population in human pancreatic islets in health and type 2 diabetes - Miljana Radenkovic; Jeanette Arvastsson; Luis Sarmiento; Corrado M Cilio (BMJ Open Diabetes Research & Care)
Introduction In type 2 diabetes (T2D), beta cell failure is often associated with islet inflammation driven by the innate immune response, with macrophages playing a significant role. However, the composition and phenotype of lymphoid immune cells in the islets of individuals with T2D have not been extensively studied. This study aims to characterize and compare the presence, phenotype, and frequency of islet-associated lymphocytes—specifically T, B, and natural killer (NK) cells—in patients with T2D and non-diabetic organ donors.Research design and methods Multicolor flow cytometry was employed to detect NK, B, and T cells in dissociated pancreatic islets from 13 T2D and 44 non-diabetic donors. The frequencies and phenotypes of T cell subsets were determined using markers for memory differentiation status and tissue-resident T cells. The frequencies of alpha and beta cells were assessed by flow cytometry, and the insulin secretion level was measured by ELISA.Results In both T2D and non-diabetic islets, CD3(+) T cells were the predominant lymphocytes, mainly central and effector memory phenotypes, with a bias toward CD8(+) T cells expressing canonical residency markers (CD69 and CD103). The frequencies of CD19(+) B cells and CD3(−) CD16(+) CD56(+) NK cells were low in both groups. The proportions of these immune and beta cells were similar between T2D and non-diabetic donors. However, T2D donors had a higher proportion of glucagon-producing alpha cells and significantly reduced glucose-stimulated insulin secretion compared with non-diabetic individuals.Conclusions In T2D islets, resident CD8(+) T cells with a central memory phenotype dominate the lymphoid immune cell population, similar to non-diabetic donors. These findings provide the first insights into the memory T cell composition in human pancreatic islets in T2D, suggesting that the diabetic condition does not significantly alter the lymphoid landscape of pancreatic islets.